Investigation of contributors to zinc protoporphyrin IX formation at optimum pH 5.5 in pork. (18th April 2019) - Akter, Mofassara; Shiraishi, Akiko; Kumura, Haruto; Hayakawa, Toru; Wakamatsu, Jun‐ichi
Abstract: We investigated zinc protoporphyrin (ZnPP) formation in pork at pH 5.5, identified the contributors to ZnPP formation, and verified the involvement of myoglobin in this process. When pork homogenate was separated into two water‐soluble fractions (>10 and <10 kDa) and an insoluble fraction, ZnPP formation was suppressed. ZnPP formation was rescued after mixing of all three fractions. Heating of the soluble <10 kDa fraction did not suppress the formation of ZnPP as opposed to heating of the soluble >10 kDa fraction, suggesting that protein(s) presents in the >10 kDa fraction contributed to ZnPP formation. Components of the soluble 10–30 kDa fractions separated by ultrafiltration were important in ZnPP formation. Exogenous myoglobin was not essential for ZnPP formation. A gel filtration study showed that soluble protein(s) with molecular weight higher than that of myoglobin was involved. Therefore, it was suggested that the soluble <10 kDa fraction, the insoluble fraction, and the soluble 10–30 kDa fraction (excluding myoglobin) are essential for ZnPP formation in pork at pH 5.5.